Genetic architecture of seed dormancy in U.S. weedy rice in different genetic backgrounds - Subudhi, Prasanta K.; Parco, Arnold; Singh, Pradeep K.; DeLeon, Teresa; Karan, Ratna; Biradar, Hanamareddy; Cohn, Marc A.; Brar, Darshan S.; Sasaki, Takuji (Wiley, 2012)
Seed dormancy (SD) is a key domestication trait closely related to preharvest sprouting tolerance. Wild and weedy rices (Oryza spp.) exhibit higher degrees of seed dormancy compared to the cultivated rice. Red rice (Oryza sativa L.), a major weed in the rice growing areas of the southern United States, was used to elucidate the genetic architecture of SD. Quantitative trait loci (QTL) analysis conducted in two recombinant inbred line (RIL) populations developed from the crosses involving two rice cultivars (Bengal and Cypress) and a red rice accession (PSRR‐1) revealed six to seven QTL for seed dormancy, which accounted for 49 to 52% of the total phenotypic variance. The magnitude of the QTL contribution to phenotypic variance was influenced by genetic backgrounds. The majority of QTL had minor effects, except the QTL linked to Rc and Sdr4. The genetic architecture for seed dormancy in U.S. red rice was distinct compared with the earlier reported weedy accessions. Four QTL were mapped onto similar positions in both populations. Both cultivars and red rice contributed alleles for increased SD. Most of the digenic epistatic interactions involved loci other than the QTL with main effects. The nucleotide polymorphisms at the Sdr4 locus could not explain the phenotypic variation for seed dormancy in our materials. The variation in SD among the rice cultivars could be attributed to segregation of minor QTL, which may be exploited to improve preharvest sprouting tolerance.